ANALISA PENGARUH PEMBANGUNAN JEMBATAN OGAN V TERHADAP KONDISI SOSIAL, EKONOMI, LINGKUNGAN DAN TEKNIS DI DESA TANJUNG KEMALA KABUPATEN OGAN KOMERING ULU - Lindawati Lindawati; Enda Kartika Sari; Adityan Prayoga (Jurnal Deformasi, 2022)
ABSTRACTA bridge is a construction that serves to continue and connect two parts of the road that are interrupted by obstacles. These barriers can be other roads, deep valleys, streams, and irrigation canals. The construction of the Ogan V Bridge in Tanjung Kemala Village aims to advance OKU Regency, as a means of connecting and facilitating mobilization between Tanjung Kemala residents in transporting their agricultural products to the traditional market of Baturaja City, facilitating access to transportation for residents across the Ogan River to Baturaja city, and support the economic development of the residents of Tanjung Kemala Village. The construction of the Ogan V Bridge certainly has a significant impact in terms of mobility, economy, social and environment for the residents of Tanjung Kemala Village. The purpose of the study was to determine how much influence the construction of the Tanjung Kemala Ogan V Bridge on the social, economic, environmental and technical conditions of the Tanjung Kemala Village community. The total population of 2,731 people using the Kreije Morgan formula, a sample of 337 people was obtained. The research data were analyzed and processed using the SPSS method, namely the Multiple Linear Regression method. The results are obtained simultaneously or partially with the value of F hit > F-table, namely all variables, namely economic, social, environmental and technical variables that affect the construction of the Ogan V Bridge with a value of F-hit > F-table, namely F-hit 4,488 and t- each hit, the t-count for social variables is 4.749, economic is 2.394, environmental is 3.819 and technical is 3.251. the contribution of social, economic, environmental and technical variables to the construction variable of the Ogan V Bridge is 84.0% while the remaining 16% is varied by other variables not included in this study